POLICY ANALYSIS OF UMAR BIN ABDUL AZIZ IN BUILDING FAMILY RESILIENCE - zuraidah, zuraidah; Alaiddin, Alaiddin; Aslati, Aslati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Family is the society life cells which are the main foundation for generations’ development and continuity. Umar Bin Abdul Aziz's leadership model, a famous caliph during the Umayyad caliphate, emphasizing the leadership based on Islamic principles which aimed to build family resilience in society. Umar bin Abdul Aziz's leadership pattern certainly brought values and messages for ideal family education. This research aimed at analyzing Umar bin Abdul Aziz's leadership model in the context of building family resilience on the perspective of Islamic family law. This research used a qualitative approach with analyzing historical documents and literature about the life and policies of Umar bin Abdul Aziz related to family and society. The research findings showed that Umar bin Abdul Aziz's policy in building family tenacity was reflected in his leadership style example, achievements and services which were often referred to as the fifth of Khulafaur Rasyidin. Umar bin Abdul Aziz's policy analysis in building family resilience during his reign as caliph played an important role in strengthening family institutions in Islamic society. These policies reflected to Islamic principles that promoted justice, protection and empowerment of families. Among these were such as providing assistance to poor families, empowering the family economy and eliminating the tax burden, and protecting the rights of women and children. By understanding Umar bin Abdul Aziz's method for building family resilience, it is hoped that we can draw inspiration and valuable lessons that can be applied in the context of modern family life.